Comparison of blood pressure in the arm and ankle in patients in the emergency department - Goldstein, Lara Nicole (My University, 2013)
Objectives: 1. To establish whether the differences between the arm and ankle noninvasive blood pressure (NIBP) measurements of Systolic Blood Pressure (SBP), Diastolic Blood Pressure (DBP) and Mean Arterial Pressure (MAP) are clinically relevant (i.e. a difference of 10 mmHg). 2. To determine whether any patient characteristics (age, sex, race, height, weight, body mass index (BMI), arm circumference, ankle circumference, presenting complaint, and tobacco usage) influence the difference between ankle and arm NIBP measurements. Design: Prospective cross-sectional study Setting: Netcare Union Hospital Emergency Department (ED) Patients: All patients from 18 to 50 years of age presenting to the ED who were not in need of emergency medical treatment and who consented to participating in the study. Methods: Patients had their blood pressure measured whilst lying in the supine position. The blood pressure was measured on both arms and ankles with the correct size cuff according to manufacturer’s guidelines. All appropriate data was recorded. Main Results: The blood pressure measurements in the arm and ankle were compared. SBP measurement in the ankle was found to be inaccurate when compared to the arm and thus cannot be used as a substitute for arm SBP. Ankle DBP is the most accurate and deviates from the actual arm DBP within the clinically acceptable range of 10 mmHg. MAP difference is clinically acceptable on average, but the 95% CI show that the range extends beyond the clinically acceptable range. Conclusions: Ankle blood pressure should not be used as a substitute for arm blood pressure in the Emergency Department.